Noble values principle and indicators as ethical guiding principles for modern biotechnology in Malaysia - Nur Asmadayana Hasim; Latifah Amin; Ahmad Fazil Ellias; Zurina Mahadi; Mashitoh Yaacob (Penerbit Universiti Kebangsaan Malaysia, 2021)
Malaysia enacted the Biosafety Act 2007 and its regulations, the Biosafety (Approval and Notifications) Regulations 2010 to ensure the biosafety of modern biotechnology in Malaysia. However, the current Act and regulations do not fully consider the ethical issues arising in modern biotechnology. Besides the four well-established principles proposed by the well-known bioethicists, Beauchamp and Childress, there are other important principles which should be taken into account. In Islam, every human is a trustee (Khalifs), whose role is to take responsibility for the protection of God’s creation and execute good values for a great civilization. The objectives of this study are to review the principle of the noble values of modern biotechnology, and develop practical indicators for this principle. The study was conducted using a descriptive literature review and Focus Group Discussions (FGD) among stakeholders. It was found that the noble values principle consists of four sub-principles, which are: 1) integrity; 2) accountability; 3) transparency and; 4) objectivity and disinterestedness.The indicators for this principle referred to two suggestions from the stakeholders, which were 1) each of the sub-principles should have its indicators, or 2) to use one line of a self-declaration from modern biotechnology practitioners as the indicator to ensure the noble values principles have been incorporated.